Ecological engineering approaches to restoring the aquatic biological community of an urban pond ecosystem and its effects on water quality ‑ a case study of the urban Xixi National Wetland Park in China - Liu Fang; Lu Jianbo (Knowledge and Management of Aquatic Ecosystems, 2021)
There is a global increase in urbanization, which contributes to the loss and fragmentation of urban wetland and pond habitats. Urban ponds have an important role in the ecology of urban areas, as they provide essential habitats for aquatic species. The objective of this study is to demonstrate ecological engineering approaches to restoring aquatic biological communities in an urban pond ecosystem, which can be used to achieve water purification of such ecosystems globally. The general approach of first cleaning out the ponds and then systematically applying different treatments of plants and fish was designed and implemented in the field. We used three replicated ponds per engineering treatment to determine which of the treatments was the best option based on an assessment of water quality and biological indicators. The main findings of this study were as follows: a combination of aquatic animals and aquatic plants can provide the best water purification performance; furthermore, macrobenthos, such as Bellamya purificata, can be used as biological indicator species for monitoring dominant species and water quality in a local urban pond ecosystem. In conclusion, maintaining biological species diversity over different trophic levels can provide the best water purification performance in urban pond ecosystems.